Considering Environmental Factors in Technical Efficiency Analysis of European Crop Production - Alexander Kaiser; Axel Schaffer (German Journal of Agricultural Economics (GJAE), 2022)
Data Envelopment Analysis (DEA) is a popular tool to determine technical efficiency of agricultural production. One issue that arises in some nonparametric frameworks is the heterogenous endowment with determinate factors, such as agroclimatic conditions. Environmental factors clearly lie outside of the sphere of influence of the decision-maker and pose natural limits to increasing efficiency and productivity of agricultural production. Calls for rationalization or better allocation of production inputs might thus not be adequate if concerned studies do not properly account for exogeneous factors of efficiency. The presented paper addresses the existing attempts to deal with the issue and analyzes the effect of soil quality on technical efficiency, calculated for crop producers of 122 European regions (FADN), using a regularly employed two-stage DEA framework. The effect of soil quality is then accounted for by adjusting the input factor land by a land quality factor. First, results show that environmental factors, e.g., soil quality, have a significant positive effect on technical efficiency. Further, the proposed land adjustment reveals structurally different results for some individual efficiency estimates, which indicates that neglecting the effect of environmental factors on efficiency might yield misleading policy implications.
Keywords: 330; technical efficiency; environmental factors; exogenousfactors; nonparametric efficiency analysis; two-stageapproach; land heterogeneity; crop production